The regulation of healthcare professions and support workers in international context - Mike Saks (BMC, 2021)
Abstract Background The objective of this paper is to outline and compare the regulation of paid healthcare professions and associated support workers in international context, bringing out the lessons to be learned as appropriate. Modern neo-liberal societies have sought to enhance healthcare through greater professional regulation, albeit in different ways and at variable pace. This general trend is illustrated with reference to medicine in the UK. However, although such reforms have helpfully cascaded to other health professions, government policy in high-income countries has not yet adequately regulated the interrelated group of non-professionalised health support workers who form the largest and least recognised part of the workforce. Nonetheless, in low- and middle-income (LMIC) countries-aside from the greater need for regulation of health professions-there is even more of an imperative to regulate the disparate, largely invisible support workforce. Methods With reference to existing studies of the medical and wider health professions in the UK and selected other higher income societies, the importance of health professional regulation to the public is underlined in the Global North. The larger gap in the regulation of support workers in modern neo-liberal countries is also emphasised on a similar basis, with an increasingly ageing population and advances in healthcare. It is argued from the very limited patchwork of secondary literature, though, that policy-makers may want to focus even more on enhancing regulation of both the professional and non-professional workforce in LMIC societies centred mainly in the Global South, drawing on lessons from the Global North. Results/conclusions Efforts to reform health professional regulatory approaches in more economically developed countries, while needing refinement, are likely to have had a positive effect. However, even in these societies there are still substantial shortfalls in the regulation of health support workers. There are even larger gaps in LMICs where there are fewer health professional staff and a greater dependence on support workers. With higher rates of morbidity and mortality, there is much more scope here for reforming health regulation in the public interest to extend standards and mitigate risk, following the pattern for healthcare professions in the Global North.